2009
DOI: 10.1038/modpathol.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

t(14;18)-negative follicular lymphomas are associated with a high frequency of BCL6 rearrangement at the alternative breakpoint region

Abstract: A frequent chromosomal translocation in mature B-cell non-Hodgkin lymphoma affects band 3q27 and results in deregulation of the B-cell lymphoma 6 (BCL6) gene. Two breakpoint clusters have been described thus far, the major breakpoint region (MBR) and an alternative breakpoint region (ABR) that is located 245 - 285 kb 5' to BCL6. Translocation at the MBR predominates in diffuse large B-cell lymphoma, whereas translocation at the ABR is reported to be frequently associated with grade 3B follicular lymphoma. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…It is noteworthy that these genetic aberrations have been associated with histologic grade 3A or 3B disease. 10,13,[37][38][39] In our current study, patients who had grade 3A or 3B tumors also frequently were t(14;18)-negative rather than t(14;18)-positive (44% vs 8%). However, we were able to identify the alternative genetic alterations (BCL6 translocation, trisomy 3 or 18) in only approximately 33% of the patients without t(14;18).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It is noteworthy that these genetic aberrations have been associated with histologic grade 3A or 3B disease. 10,13,[37][38][39] In our current study, patients who had grade 3A or 3B tumors also frequently were t(14;18)-negative rather than t(14;18)-positive (44% vs 8%). However, we were able to identify the alternative genetic alterations (BCL6 translocation, trisomy 3 or 18) in only approximately 33% of the patients without t(14;18).…”
Section: Discussionsupporting
confidence: 49%
“…However, we were able to identify the alternative genetic alterations (BCL6 translocation, trisomy 3 or 18) in only approximately 33% of the patients without t(14;18). It has been reported that 26% to 68% of FLs without t(14;18) lack expression of the BCL2 protein, 10,37,38 although we did not enroll such BCL2-negative patients in this study. In our 2 patients who had extra copies of BCL2 (partial trisomy 18), amplification of the BCL2 gene may have contributed to overexpression of the BCL2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several publications since 2001 suggested that grade 3B FL is biologically distinct from grades 1-3A, with features suggesting a close relationship to DLBCL (more frequent lack of CD10 and BCL2, expression of IRF4/ MUM1, and rearrangement of BCL6 but not BCL2). [17][18][19][20] These considerations led to the recommendation to group together FL grade 1-3A as "FL" and to create a new category for what has been called FL3B. Although this idea was attractive to both pathologists and clinicians, there were several arguments against it.…”
Section: Follicular Lymphoma: Grading and Variantsmentioning
confidence: 99%
“…Its molecular consequence is the juxtaposition of the B-cell lymphoma/leukemia 2 (BCL2) proto-oncogene with enhancer sequences of the immunoglobulin heavy chain gene (IGH) promoter region, thereby deregulating its expression and resulting in an overexpression of the BCL2 protein in the neoplastic follicles [52,53]. However, 10-15% of cases do not harbor the t(14;18)(q32;q21) and in these t(14;18)-negative cases, other mechanisms are thought to be involved in the pathogenesis [54]. Moreover, t(14;18)-positive B cells can be identified in the blood and lymphoid tissues of healthy individuals, and the number of t(14;18)-positive cells is influenced by gender, personal lifestyle and exposure to toxic substances [55].…”
Section: Cytogenetics Of Follicular Lymphomamentioning
confidence: 99%